A relação humano-animal pela ótica dos lares unipessoais - Cavalcante, Pedro Paulo Santos (2023)
This study aims to identify the dimensions that most explain the human-pet relationship in the homes of people who live alone in Brazil. To this, we conducted a survey to 690 interviewees at national level, using international psychometric scales. As a result, the dimensions pet oriented lifestyle and anthropomorphism were those that most explained the human-animal relationship. This study demonstrates that there are no significant behavioral differences between the group of people who live by themselves and different family arrangements. However, this study indicates that people who live by themselves tend to spend more on their pets than on other household arrangements. Another important finding is the fact that pet owners’ budgets do not include fully spending on pets. The results of this study also suggest that the process of purchasing products and services for pets passed through a much more emotional sphere than a rational one. Finally, this study proved that, despite having been originally developed for dogs, with some considerations, the psychometric scales also work for cat owners. Finally, we recommend that future studies validate the application of these scales to pet owners of other types of animals.